The Value of Solidarity in Learning Activities Integrated with Traditional Games - Puri Minang; Edhy Rustan; Hisbullah Hisbullah (Jurnal Ilmiah Sekolah Dasar, 2023)
The role of technology has affected the value of student solidarity, so it is necessary to integrate learning activities with traditional games. The purpose of this study was to formulate cooperative learning activities of the TGT type integrated with traditional fortification games to increase student solidarity's value. This type of research is descriptive qualitative. The subjects of this research were 20 students of class V. Data collection in the study was carried out using observation, interview, and documentation methods with research instruments in the form of interview guides, guidelines for observing the implementation of student solidarity values, and documentation of learning tools. The collected research data were analyzed thematically. The results show that the teacher's learning activities could be more optimal. Indicators of solidarity values,  togetherness, mutual respect, and helping each other have yet to be fulfilled properly. Cooperative learning of the TGT type is integrated with traditional games of fortifications, which should be carried out consisting of opening learning with religiously charged activities, providing apperception and motivation, conveying titles and subject material, dividing groups by suit, discussion, questions overtakes, evaluation of material, awarding, review, as well as providing reflection and motivation. The formulation of the TGT-type cooperative learning activities integrated with traditional fortification games can be a solution to increasing the value of student solidarity.